É para isolar as variáveis, fazer a substituição e depois calcular.
2a - 7b = 2
a - 3b = - 3
- x + 5y = - 1
- 2x - 3y = 5
Soluções para a tarefa
Respondido por
1
2a - 7b = 2 -x + 5y = -1 ⇒ -x= -1-5y ⇒ x = 1 + 5y
a - 3b = - 3 ⇒ a = -3 + 3b -2x - 3y = 5
2·(-3+3b) - 7b = 2 -2·(1+5y) - 3y = 5
-6 + 6b -7b = 2 -2 -10y - 3y = 5
-b = 8 ·₍₋₁₎ -13y = 7 ₍₋₁₎
b = -8 y = 7/13
a - 3b = -3 -x +5y = -1
a + 24 = -3 -x + 35/13 = -1
a = -27 -13x + 35 = -13
-13x = 48
x = 48/13
a - 3b = - 3 ⇒ a = -3 + 3b -2x - 3y = 5
2·(-3+3b) - 7b = 2 -2·(1+5y) - 3y = 5
-6 + 6b -7b = 2 -2 -10y - 3y = 5
-b = 8 ·₍₋₁₎ -13y = 7 ₍₋₁₎
b = -8 y = 7/13
a - 3b = -3 -x +5y = -1
a + 24 = -3 -x + 35/13 = -1
a = -27 -13x + 35 = -13
-13x = 48
x = 48/13
Perguntas interessantes
História,
11 meses atrás
Matemática,
11 meses atrás
Química,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás